The Effect of Medicinal Herb Inclusion on Hematologic Status and Blood Lipid Profiles in Broiler Chickens - Santoso , Urip; Fenita, Yosi; Kususiyah (International Journal of Poultry Science, 2017)
Background and Objective: The use of antibiotics as a feed supplement in broiler chickens is not recommended and therefore, antibiotics should be substituted with alternative compounds. The present study was conducted to evaluate the effect of medicinal herb powder inclusion on hematological status, blood lipid profiles, internal organ weight and toxicity score in female broiler chickens. Materials and Methods: One hundred sixty-eight female broiler chickens aged 15 days were distributed into 7 groups. Each treatment group consisted of 4 replicates and each replicate consisted of 6 broilers. The 7 treatments were as follows: 1) broilers were fed a diet with no medicinal herbs as the control (P0), 2) broilers were fed with 5% Sauropus androgynus (S. androgynus) leaf powder (P1), 3) broilers were fed a diet with 5% bay leaf powder (P2), 4) broilers were fed a diet with 5% basil leaf powder (P3), 5) broilers were fed a diet with 5% papaya leaf powder (P4), 6) broilers were fed a diet with 5% Moringa leaf powder (P5) and 7) broilers were fed a diet with 5% noni fruit powder. Results: Sauropus androgynus leaf contained the highest protein content, at 34.37%, while noni fruit and basil leaf were rich in iron, at 7.80 and 6.43 ppm, respectively, followed by papaya leaf and Sauropus androgynus leaf, at 5.61 and 4.02 ppm, respectively. The noni fruit contained the highest crude fiber content (19.33%) followed by bay leaf (17.73%) and Sauropus androgynus leaf (14.16%). Experimental results showed that medicinal herb inclusion affected WBC (p